Menuju Pembelajaran Yang Efektif: Menelaah Hubungan Gaya Belajar dan Motivasi Belajar Terhadap Hasil Belajar Peserta Didik di MAN 2 Kota Malang - Aji Saputra, Mochammad Ronaldy; Dwijayanti, Meytikasari; Suryadi (UIN Kiai Haji Achmad Siddiq Jember, 2024)
This research aims to analyze the relationship between learning styles learning motivation and student learning outcomes at MAN 2 Kota Malang. This research uses a quantitative research design with a correlational approach. The research sample was taken simply randomly as many as 100 people. The instruments used include learning style questionnaires, learning motivation questionnaires, and learning outcomes tests. Data analysis was carried out using multiple linear regression tests. The results of the research show that (1) there is a significant relationship between learning style and learning motivation and student learning outcomes, (2) learning style and learning motivation simultaneously influence student learning outcomes, and (3) visual learning style and motivation Intrinsic is the most dominant factor influencing student learning outcomes. The implication of this research is the importance of a learning approach that pays attention to individual learning styles and learning motivation so that it can grow student learning outcomes at MAN 2 Kota Malang